2021
DOI: 10.1111/acel.13490
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular iron injection induces oxidative stress followed by elements of geographic atrophy and sympathetic ophthalmia

Abstract: Iron has been implicated in the pathogenesis of age-related retinal diseases, including age-related macular degeneration (AMD). Previous work showed that intravitreal (IVT) injection of iron induces acute photoreceptor death, lipid peroxidation, and autofluorescence (AF). Herein, we extend this work, finding surprising chronic features of the model: geographic atrophy and sympathetic ophthalmia. We provide new mechanistic insights derived from focal AF in the photoreceptors, quantification of bisretinoids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 38 publications
0
31
2
Order By: Relevance
“…Moreover, we found that IVT iron-induced damage appears to be less severe with the DHA diet than our previous study in mice fed with "regular chow" (LabDiet 5001) (Liu et al, 2021). We previously observed ironinduced retinal AF throughout the retina in mice fed with LabDiet 5001 at 1 week after iron injection, and "kidney bean" shaped geographic atrophy always occurred at 4 weeks after iron injection (Liu et al, 2021). In the current study, we observed that iron-induced AF was more limited to the superior retina in mice fed with DHA for 4 weeks at 1 week after iron injection (Figure S2), and the "kidney (Angelova et al, 2015;Shchepinov et al, 2011), Alzheimer's disease (Elharram et al, 2017;Raefsky et al, 2018), Huntington's disease (Hatami et al, 2018), and infantile neuroaxonal dystrophy (Kinghorn et al, 2015).…”
Section: D-dha Prevented Iron-induced Geographic Atrophy Developmentcontrasting
confidence: 58%
See 3 more Smart Citations
“…Moreover, we found that IVT iron-induced damage appears to be less severe with the DHA diet than our previous study in mice fed with "regular chow" (LabDiet 5001) (Liu et al, 2021). We previously observed ironinduced retinal AF throughout the retina in mice fed with LabDiet 5001 at 1 week after iron injection, and "kidney bean" shaped geographic atrophy always occurred at 4 weeks after iron injection (Liu et al, 2021). In the current study, we observed that iron-induced AF was more limited to the superior retina in mice fed with DHA for 4 weeks at 1 week after iron injection (Figure S2), and the "kidney (Angelova et al, 2015;Shchepinov et al, 2011), Alzheimer's disease (Elharram et al, 2017;Raefsky et al, 2018), Huntington's disease (Hatami et al, 2018), and infantile neuroaxonal dystrophy (Kinghorn et al, 2015).…”
Section: D-dha Prevented Iron-induced Geographic Atrophy Developmentcontrasting
confidence: 58%
“…To evaluate whether D-DHA could protect against geographic atrophy in this model, mice were continued on their respective diets for 4 weeks after iron or saline injection. IVT iron-induced retinal AF, oxidative stress, accumulation of carboxyethylpyrrole (CEP), a DHA-specific oxidation product, and photoreceptor degeneration followed by progressive geographic atrophy, replicating features of human AMD (Liu et al, 2021). In this study, we have found that dosing of D-DHA completely protected against all these iron-induced retinal changes.…”
Section: D-dha Prevented Iron-induced Geographic Atrophy Developmentmentioning
confidence: 57%
See 2 more Smart Citations
“…The amount of retinal injury and rate of progression associated with systemic iron loading appears to be varied depending on the specific regulatory protein involved, in addition to the age and sex of the mice (Hahn et al, 2009). While there is an increasing interest in incorporating electroretinography and in vivo imaging, as well as gene expression changes in retinal studies in animal models of iron loading (Liu et al, 2021), the number of such studies are still limited. More comprehensive time course studies, particularly using complementary tools such as electroretinography and in vivo imaging to define the earliest retinal deficits would help to define the role of iron regulation on retinal degeneration.…”
Section: Summary Of Animal Studies On Iron and Retinamentioning
confidence: 99%